A comparison study on adsorption and interaction behaviors of diluted bitumen and conventional crude oil on model mineral surface. (1st October 2019) - Huang, Jun; Stoyanov, Stanislav R.; Zeng, Hongbo
Graphical abstract: Highlights: DB exhibits adsorption and interaction behavior distinct from that of CCO. Petroleum molecules quickly adsorb onto a mica surface in about 5 min. The interaction forces for oil solutions are concentration dependent. Asphaltenes are critical for oil interaction behavior on mineral solids. Abstract: The increasing volume of petroleum products being transported from the Canadian oil sands raises concerns of potential impacts of accidental oil discharges in-land. Understanding the adsorption behavior of petroleum on mineral surfaces is important for oil spill modeling and response. In this work, a comparison study is conducted to probe the interaction behaviors of two distinct petroleum products, diluted bitumen (DB) and conventional crude oil (CCO), with molecularly smooth mica surfaces (as a model mineral) in toluene solutions using a surface forces apparatus (SFA) and an atomic force microscope (AFM). It is observed that DB exhibits adsorption behavior distinct from that of CCO at the tested concentrations. At low concentrations of oil in toluene (e.g., 0.1 v/v%), the adsorbed DB film on mica is twice as thick as the CCO film on mica. Weak adhesion (<1 mN/m) is measured when separating two oil-adsorbed mica surfaces in toluene. Alternatively, when the concentration of oil is increased to 10 v/v%, the initial oil-film thickness is doubled for the two oils tested. Adhesion (∼10 mN/m) with long stretching or bridging (>70 nm) is observed in DB-toluene but not in CCO-toluene. The distinct adsorption behavior of DB is demonstrated to be mainly due to the high concentration of surface-active components, such as asphaltenes. The AFM imaging and Fourier-transform infrared spectroscopy results further support the SFA results. Our study provides fundamental insights into the adsorption and interaction behaviors of DB and CCO on mineral surfaces, with implications for predicting oil spill behavior and improving spill response measures.